ORGANIC LETTUCE PRODUCTION OVER BLACK OAT TILLAGE, AND DIFFERENT SOIL COVERING - MÓGOR, Átila Francisco; CÂMARA, Francisco Luiz Araújo (Scientia Agraria, 2007)
The goal of this research was to evaluate the effect of the soil covering with black oats straw, and soil covered with black plastic, in growth, production and nitrogen content of the lettuce in organic production system. There have been defined five handling systems for soil covering: without cover, covered with black plastic, covered with laying oats, covered with harvested oats, and covered with oats straw in natural form, for growing three cultivars of lettuce. The trial was conducted on the Brazilian Association of Biodynamic Agriculture (ABD), Botucatu – SP. It was used the randomized blocks design in split plot system, with four replications. It has been concluded, that all soil covering systems raised better lettuce production them uncovered soil. Soil covered with black plastic raised better lettuce production among the soil covering systems. In tilled soils, the butter head lettuce showed better production over soil covered with laying oats, the green leaf lettuce shoed better production over soil covered with laying oats, and covered with oats straw in natural form, and the iceberg lettuce showed better production over soil covered with harvested oats and covered with oats straw in natural form.